THE POTENTIAL USE OF BEEF TALLOW FOR BIODIESEL PRODUCTION IN BRAZIL - Carraro, Alecyr dos Reis; César, Aldara da Silva; Conejero, Marco Antonio; Ribeiro, Eliene Cristina Barros; Mozer, Thiago Simonato (Revista Valore, 2021)
Biodiesel has been presented worldwide as a viable alternative to petroleum-based fuels. In 2018, the main raw materials in this Brazilian sector was soybean (70.52%) and beef tallow (13.4%). The Brazilian mandatory biodiesel-diesel blend is currently 10% (B10), but B20 is estimated for 2030. Additionally, the National Program for the Production and Use of Biodiesel (PNPB) intends to promote the diversification of raw materials in the energy matrix, where the beef tallow - a residue of the beef production - has been increasing importance. Brazil presents as the global largest commercial beef producer and exporter. Then, the use of beef tallow would allow the expansion of biodiesel production without fuel x food competition and provide a nobler use than disposal for it. In this sense, this article analyzes, through a review, the potential of beef tallow for biodiesel production in Brazil. This raw material has price, quantity and quality for generating a biodiesel in the specifications required by regulatory agencies. Therefore, beef tallow is a potential raw material for the expansion of the biodiesel sector in Brazil and this experience can be useful for other countries.